Peran Keluarga Terhadap Kepatuhan Remaja Menerapkan Protokol Kesehatan - Wilda Rezki Pratiwi; Siti Hasriani; Asnuddin Asnuddin (Universitas Islam Madura, 2022)
The Covid-19 outbreak is a new and highly contagious disease that has changed people's lifestyles. One of the health protection efforts that can be done is by using personal protective equipment (PPE), cleaning hands, keeping distance and increasing body resistance. families have an important role in supporting government policies for behavior change. To analyze the role of the family on adolescent compliance, apply a health protocol. The method used in this study is an analytical observational research method with a cross sectional design with a population of 98 people. Sample : 72 people. Determination of the sampling technique using cluster random sampling. The criteria for the sample in this study are children aged 10-19 years, living with their parents, willing to be research respondents. Respondents will be given a questionnaire that has been tested for validation and reliability, then will be tested for Chi Square statistics. Data analysis technique using Chi-Square. Results: Chi Square test between the variables studied sig value (2-tailed) 0.010, which means that there is an influence of the role of parents on adolescent compliance. Conclusion: It is hoped that the family as the smallest part of society can take an active role in dealing with the Covid-19 problem. What can be done is to be able to discipline all family members and educate or educate their children to comply with the health protocols set by the government. Keywords: Family Role, Teenager, Health Protocol